Utilização de práticas de gerenciamento de projetos aplicadas em projetos de responsabilidade social corporativa: um estudo de caso em uma empresa brasileira - Figueiredo, Ana Clara Chaves de (2015)
The study aims to present an overview of the relevance of the themes social responsibility and project management. Introducing the justification for the need to segregate the two issues in the management of social responsibility projects, the study addresses not only the issue of implementation of social responsibility in business, but also seeks to measure the level of use of management practices in project social responsibility in a Brazilian company. The study presents the main concepts that address corporate social responsibility, as well as the concepts that address the topic Project Management. As the theme Corporate Social Responsibility is no longer for companies just a matter of philanthropy but of organizational and strategic management, this study directs to survey the relevance of the topic and the need to apply concepts and practices in project management of social responsibility. The question explored in the developed case study is how the company use practices and project management methodologies applied to social responsibility projects. To evaluate the scenario of Brazilian organizations, the paper submitted a case study of a Brazilian organization that develops many projects in social responsibility and has the social responsibility actions defined in its organizational strategy. The result obtained in the case study showed that although the company has begun the process of knowledge transfer and standardization of project management practices, the perception of managers and the search result reflected that these practices should be matured in corporate projects environment.